Advancing Pedagogical Alignment in a Bhutanese Teacher Education College: Employing an Action Research Approach Anchored in Bloom's Taxonomy - Tshering, Gembo; Tshewang, Rinchen; Dendup, Tashi; Peljor, Tandin (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
Tutors in higher education institutions often face the challenge of aligning learning outcomes, subject matters, instructional activities, and assessment practices. Drawing from a decade of teaching experience, the authors employ practical action research (PAR) to develop a common anchor for achieving alignment. Their project unfolds in three phases: baseline data collection, intervention development and use, and post-intervention evaluation. Baseline data analysis revealed the intricacies of evaluating alignment within class lessons, emphasizing the need to reevaluate current practices. The interventions, mapped to the cognitive and knowledge dimensions of Bloom’s Taxonomy of Educational Objectives, were transformative tools aimed at achieving alignment. Post-intervention data analysis demonstrated tangible changes in lesson outlines and responses to follow-up questions, validating the effectiveness of the interventions. The authors underscore the importance of Bloom’s Taxonomy of Educational Objectives as a facilitator for alignment, offering tutors a practical and straightforward approach. The authors conclude by proposing the scalability of this approach during semester planning, providing tutors with a systematic framework to achieve alignment. Additionally, they suggest avenues for future research, exploring beyond the cognitive and knowledge dimensions to enhance the alignment phenomenon in educational practices.